Facile synthesis of CsPbBr3/PbSe composite clusters - Thang Phan Nguyen; Abdullah Ozturk; Jongee Park; Woonbae Sohn; Tae Hyung Lee; Ho Won Jang; Soo Young Kim (Science and Technology of Advanced Materials, 2018)
In this work, CsPbBr3 and PbSe nanocomposites were synthesized to protect perovskite material from self-enlargement during reaction. UV absorption and photoluminescence (PL) spectra indicate that the addition of Se into CsPbBr3 quantum dots modified the electronic structure of CsPbBr3, increasing the band gap from 2.38 to 2.48 eV as the Cs:Se ratio increased to 1:3. Thus, the emission color of CsPbBr3 perovskite quantum dots was modified from green to blue by increasing the Se ratio in composites. According to X-ray diffraction patterns, the structure of CsPbBr3 quantum dots changed from cubic to orthorhombic due to the introduction of PbSe at the surface. Transmission electron microscopy and X-ray photoemission spectroscopy confirmed that the atomic distribution in CsPbBr3/PbSe composite clusters is uniform and the composite materials were well formed. The PL intensity of a CsPbBr3/PbSe sample with a 1:1 Cs:Se ratio maintained 50% of its initial intensity after keeping the sample for 81 h in air, while the PL intensity of CsPbBr3 reduced to 20% of its initial intensity. Therefore, it is considered that low amounts of Se could improve the stability of CsPbBr3 quantum dots.